Confirmatory analysis of the instrument Coping with Stress (COPE) in women with violence in relationship - Canelo Espinoza, Gretty A. (2018)
The use of psychological instruments in clinical work, in this case in women with violence in the couple relationship, puts us in constant verification of the construct validity of possible instruments that help to know the coping strategies in these cases. The objective of this study was to evaluate an aspect of construct validity, through multivariate techniques, of the Stress Coping Questionnaire in 267 women, whose ages ranged from 18 to 70 years of age. The COPE questionnaire (full version) was used, which consists of 52 items characterized in three coping styles with a dichotomous response. It was confirmed by the use of the Confirmatory Factor Analysis and the adjustments of the global model (Cmin = 1.83), comparative (CFI = .93, GFI = .91 and TLI = .91) and other indices (RMR = 0.04 and RMSEA = .06) yielded acceptable and good results. Thus, it is concluded that the COPE questionnaire in its full version is a valid instrument for the measurement of coping strategies for stress in women with relationship violence.